On the Inertia Term of Projectile's Penetration Resistance - Yu Shan; Haijun Wu; Fenglei Huang; Jinzhu Li (Advances in Materials Science and Engineering)
The effect of the target inertia term of rigid kinetic energy projectiles (KEP’s) penetration resistance is investigated using nonlinear dynamic code LS-DYNA and four constitutive models. It is found that the damage number of target can be used to measure the influence of the inertia term. The smaller the damage number is, the less influence the inertia term has. The less dependent the resistance has on projectile velocity, the more accurate it is to treat the resistance as a constant. For the ogive-nose projectile with CRH of 3, when the target is aluminum, steel, or other metals, the threshold velocity for the constant resistance is at least 1258 m/s; when the target is concrete, rock, or other brittle materials, if the velocity of the projectile is greater than 400 m/s or so, the damage number would be very large, and the penetration resistance would clearly depend on the projectile’s velocity. The higher the elastic wave velocity is, the more penetration process is affected by the impact face.